'New mining scheme, same old problems?'; risk factors and health challenges in underground community mining in Ghana - Simon Appah Aram; Benjamin M Saalidong; Akwasi Yankyera; Akwasi Bamfo Akoto; Samuel Kofi Amoah (IOP Publishing, 2024)
Ghana's small-scale mining sector has long been a cornerstone of its economy and a vital source of livelihood for many communities. However, the sector is plagued by significant challenges, including environmental degradation, health and safety risks, and illegal practices. In response, the Ghanaian government introduced the Community Mining Scheme (CMS), a new mining model designed to promote local community participation in artisanal small-scale gold mining (ASGM). This study examines the workplace risk factors and associated health challenges faced by ASGM miners under the CMS, drawing on interviews with fifty underground CMS miners in Ghana. Our findings reveal that miners continue to face numerous health and safety challenges, including inadequate lighting, poor ventilation, exposure to noise and odors, unsupported or poorly supported loose materials, non-use of personal protective equipment, high dust levels, and unsafe blasting practices. Additionally, health concerns such as skin rashes, musculoskeletal injuries, and the risk of mercury poisoning persist. These challenges mirror those reported in the literature on unregulated and illegal ASGM in Ghana, indicating that existing issues remain unresolved under the CMS. To prevent the undermining of this initiative, it is crucial to adopt progressive practices, such as localized coping strategies and the recruitment of trained professionals to lead ASGM operations within the CMS. Enhancing miners' risk perception through targeted outreach and awareness campaigns is also essential. Further recommendations for mitigating safety risks and health challenges are discussed in the article.